Analisis Budaya Organisasi Karyawan PT. Exedy Manufacturing Indonesia - Wilda Nur Fatimah; Uus Mohammad Darul Fadli (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2024)
The social relationships created in an organization need a cultural bond to achieve the desired goals. The purpose of this research is to determine the application of organizational culture at PT. Exedy Manufacturing Indonesia. The research design uses quantitative methods with factor analysis. Research location at PT. Exedy Manufacturing Indonesia. Data was collected through observation and questionnaires. The research population was all employees at the company PT. Exedy Manufacturing Indonesia. Samples were taken randomly from various departments with a total of 100 respondents. The research results show that the three organizational culture factors that exist at PT. Exedy Manufacturing Indonesia namely Team Orientation, Stability, Innovation and risk taking. Component (factor) 1 has a correlation value of 0.799 > 0.5. Component (factor) 2 has a correlation value of 0.738 > 0.5. Component (factor) 3 has a correlation value of 0.739 > 0.5. These three factors include internal and external factors, so they can be used as a reference for PT. Exedy Manufacturing Indonesia to carry out improvements and developments.